GM2 Gangliosidosis in Shiba Inu Dogs with an In‐Frame Deletion in HEXB. (20th August 2017) - Kolicheski, A.; Johnson, G.S.; Villani, N.A.; O'Brien, D.P.; Mhlanga‐Mutangadura, T.; Wenger, D.A.; Mikoloski, K.; Eagleson, J.S.; Taylor, J.F.; Schnabel, R.D.; Katz, M.L.
Abstract : Consistent with a tentative diagnosis of neuronal ceroid lipofuscinosis (NCL), autofluorescent cytoplasmic storage bodies were found in neurons from the brains of 2 related Shiba Inu dogs with a young‐adult onset, progressive neurodegenerative disease. Unexpectedly, no potentially causal NCL‐related variants were identified in a whole‐genome sequence generated with DNA from 1 of the affected dogs. Instead, the whole‐genome sequence contained a homozygous 3 base pair (bp) deletion in a coding region of HEXB . The other affected dog also was homozygous for this 3‐bp deletion. Mutations in the human HEXB ortholog cause Sandhoff disease, a type of GM2 gangliosidosis. Thin‐layer chromatography confirmed that GM2 ganglioside had accumulated in an affected Shiba Inu brain. Enzymatic analysis confirmed that the GM2 gangliosidosis resulted from a deficiency in the HEXB encoded protein and not from a deficiency in products from HEXA or GM2A, which are known alternative causes of GM2 gangliosidosis. We conclude that the homozygous 3‐bp deletion in HEXB is the likely cause of the Shiba Inu neurodegenerative disease and that whole‐genome sequencing can lead to the early identification of potentially disease‐causing DNA variants thereby refocusing subsequent diagnostic analyses toward confirming or refuting candidate variant causality.